SKRINING FITOKIMIA DAUN KERSEN (Muntingia calabura L.) METODE MASERASI - Lily Yulia Surya Sari (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2026)
PHYTOCHEMICAL SCREENING OF KERSEN LEAVES (Muntingia calabura L.) MACERATION METHOD ABSTRACT The cherry plant (Muntingia calabura L.) is a plant that is often used by Indonesian people as a plant that is useful as a traditional medicine. This cherry plant contains secondary metabolites or bioactive compounds such as alkaloids, flavonoids, saponins, tannins, and triterpenoids/steroids. The aim of this research was to determine the content of bioactive compounds contained in the ethanol extract of cherry leaves (Muntingia calabura L.) This type of research is descriptive. The method used in this research is maceration to obtain a thick extract from cherry leaves. Maceration uses 96% ethanol as a solvent. The extract obtained from the ethanol solvent was then tested for phytochemical screening with several reagents. Phytochemical screening in this study was carried out to qualitatively identify bioactive compounds contained in the ethanol extract of cherry leaves. The bioactive compounds identified include alkaloids, flavonoids, saponins, tannins, and triterpenoids/steroids. The results of this study indicate that the ethanol extract of cherry leaves (Muntingia calabura L.) contains bioactive compounds in the form of alkaloids, flavonoids, saponins, tannins and steroids. Keywords: Kersen leaves, maceration, phytochemical screening.